Consumer Dissatisfaction: The Effect of Disconfirmed Expectancy on Perceived Product Performance - Anderson, Rolph E. (Journal of Marketing Research, 1973)
Four psychological theories are considered in determining the effects of disconfirmed expectations on perceived product performance and consumer satisfaction. Results reveal that too great a gap between high consumer expectations and actual product performance may cause a less favorable evaluation of a product than a somewhat lower level of disparity.